Comprehensive characterization of the Lidar TF Mini sensor for its potential use in early breast cancer detection, employing a data-driven approach - Annas, Muhamad Azwar; Marufah, Asmaul Lutfi; Chasanah, Uswatun (Universitas Sultan Ageng Tirtayasa, 2025)
Breast cancer is a leading cause of death among women. Early detection helps prevent the spread of cancer to other organs, thereby reducing serious risks. This characterization aims to determine the potential of the TF Mini Lidar sensor if used as an early detection tool for breast cancer. Basically, this characterization uses a data-based approach. The method used in this study is to position the TFmini and HC-SR04 sensors in a fixed and stable position, after which the reflective object is positioned at a predetermined distance according to the distance to be used when detecting breast cancer, which is at a distance of 51-100 cm. PLX daq version 2.11 was used to facilitate data collection. The characterization of this sensor is based on the standard deviation, relative standard deviation, error and accuracy. This study concludes that the TFmini lidar sensor has a high potential to be used in breast cancer detection devices as a contour detector. This is in accordance with the measurement accuracy value of the tfmini sensor of 99.87%. However, additional sensors, such as cameras, are needed to obtain better contours and visual images.